Unilateral Anterior Scleritis Following the Booster Shot of Inactivated COVID-19 (Sinopharm) Vaccine in a 52-Year-Old Woman: A Case Report - Kimia Jazi; Mahnaz Rahimi; Fatemeh Hasani; Maryam Shirmohammadi; Maryam Masoumi (Case Reports in Rheumatology)
The only way to mitigate the spread of coronavirus disease 2019 (COVID-19) pandemic was vaccines. While effective in decreasing the rate and severity of the disease, there also have been considerable adverse events. Since the birth of vaccines, adverse reactions accompanied the immunity, and COVID-19 vaccines are no exceptions. This is a report about a 52-year-old female patient who presented with bilateral redness of the eyes, with normal bilateral visual acuity, postbooster dose of the Sinopharm COVID-19 vaccine. She had no significant past history of any disease or any similar reactions after previous doses. All her physical examinations were normal. Ophthalmic examination disclosed diffuse erythema, and mild scleral edema consistent with bilateral anterior diffused scleritis with negative phenylephrine test. Thereafter, with a course of tapering doses of prednisolone (30 mg at the onset) combined with azathioprine (100 mg/day), over a 2-week period, the condition completely resolved. Very few vaccination-related adverse events may manifest an unrecognized underlying autoimmune vasculopathy which may also require urgent management. As in this case, ocular adverse events, as highlighted, are highly associated with undiagnosed autoimmune diseases and therefore warrant careful assessment by clinicians.